The context effect as interaction of temporal generalization gradients: testing the fundamental assumptions of the Learning-to-Time model - Vieira de Castro, Ana Catarina (2013)
To test the Learning-to-Time model, six pigeons learned two temporal bisection tasks. In one task they learned to choose a Red key over a Green key following 2-s samples and the Green key over the Red key following 6-s samples; in another task, they learned to choose a Blue key over a Yellow key following 6-s samples and the Yellow key over the Blue key following 18-s samples. After each task was learned, temporal generalization gradients were obtained with samples ranging from 0.7 s to 51.4 s. Finally, preference for Green over Blue - the keys associated with the common 6-s duration, was determined as a function of sample duration. Two issues were examined, whether the preference for Green over Blue increased with sample duration, a transposition-like effect reported before, and whether the preference for Green over Blue could be predicted from the generalization gradients for Green and Blue previously obtained. Results showed that preference for Green over Blue increased with sample duration and that the general shape of the function could be predicted from the generalization gradients. The Learning-to-Time model accounted well for the major trends in the data.